PERTANGGUNGJAWABAN PIDANA BAGI PELAKU TINDAK PIDANA PEMBUNUHAN DISERTAI MUTILASI - Mochammad Sukedi; Irwan Effendi (INTELIGENSIA MEDIA, 2024)
The crime of murder is a criminal act of a material nature that awaits the consequences of the action taken, namely that the victim must die. The crime of murder accompanied by mutliation is a crime that is considered abnormal and is carried out cruelly by the perpetrator by cutting off parts of the victim's body. To determine the responsibility of the perpetrator of the crime of murder accompanied by mutilation, the condition of the perpetrator must first be known when committing the crime, which will then determine the perpetrator's ability to take responsibility for the actions he has committed. This research uses a normative legal research method by reviewing and analyzing secondary data containing primary legal materials, secondary legal materials and tertiary legal materials. Then a statutory approach and a case approach are taken. After the data is collected, it is then described in a normative-descriptive manner to explain the problem being studied. The results of the research and discussion regarding the regulation of criminal acts of murder accompanied by mutilation in positive law in Indonesia, crimes against life are regulated in Articles 338-340 of the Criminal Code, however, these acts are not regulated at all, because these criminal acts are crimes that are classified as abnormal and are committed with so heinous that special rules are needed to regulate this action. Furthermore, regarding the criminal responsibility of perpetrators of murder accompanied by mutilation, their health and mental health must be checked first in carrying out the criminal act so that it will have an impact on their ability to be responsible if based on Article 44 of the Criminal Code which regulates inability to take responsibility, but if they are deemed not to have fulfilled this article then the perpetrator can be held accountable